2020
DOI: 10.1111/jocd.13275
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral hydrolyzed eggshell membrane on the appearance of hair, skin, and nails in healthy middle‐aged adults: A randomized double‐blind placebo‐controlled clinical trial

Abstract: Background Many over the counter and consumer packaged goods are promoted to enhance the appearance of hair, skin, and nails for the consumer. Nutrition is a major factor in affecting the health and appearance of hair, skin, and nails. In addition to how one eats, dietary supplementation may play a role in overall health and in the physical appearance. Aims It was the aim of this study to objectively and subjectively evaluate the impacts of a nutritional intervention as compared to placebo on the appearances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…According to Canfield's hair density measurement system, 13 the plastic surgeon counted the number of hairs in the same quadrant (area of about 2 × 2 cm) before treatment, and 3 and 6‐month periods after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…According to Canfield's hair density measurement system, 13 the plastic surgeon counted the number of hairs in the same quadrant (area of about 2 × 2 cm) before treatment, and 3 and 6‐month periods after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…HEPs have antibacterial activity, such as excellent performance against E. coli , and exhibit a great potential in the development and application of veterinary drugs, antibacterial agents, and anti-inflammatory functional foods. Furthermore, two clinical double-blind trials demonstrated that ESMPs can improve skin wrinkles in women (30~60 years old) and be used as a dietary supplement to relieve the symptoms of osteoarthritis patients [ 158 , 159 ]. And some HEPs can enhance the absorption of dietary iron and calcium.…”
Section: Potential Applications Of Peptidesmentioning
confidence: 99%
“…The anti-inflammatory properties of ovotransferrin in egg white and in eggshell membrane have shown to possess antimicrobial and antioxidant activities in vitro and in mice [117] and has therefore been suggested for promoting skin health [16]. In human, oral hydrolyzed eggshell membrane ingestion has been associated with a significant improvement in facial skin appearance in crow's feet in 4 weeks and skin tone in 8 weeks, with significant impact on hair thickness, reduction in hair breakage and improvement in hair growth at 4, 8, and 12 weeks [118]. Natural ESM can alternate the skin barrier function restoring the skins' health and its biomechanical properties by restoring the expression of antioxidant enzymes [119].…”
Section: Skin Healthmentioning
confidence: 99%